2023
DOI: 10.1002/adsc.202300140
|View full text |Cite
|
Sign up to set email alerts
|

Gold and Biocatalysis for the Stereodivergent Synthesis of Nor(pseudo)ephedrine Derivatives: Cascade Design Toward Amino Alcohols, Diols, and Diamines

Abstract: The combination of gold(I) and enzyme catalysis has provided access to a series of nor(pseudo)ephedrine derivatives in a regio‐ and stereoselective manner. The approach involves developing IPrAuNTf2‐catalyzed hydration of 1‐phenylprop‐2‐yn‐1‐yl acetate or N‐(1‐phenylprop‐2‐yn‐1‐yl)acetamide, followed by (dynamic) asymmetric biotransamination or bioreduction of the corresponding keto ester or keto amide intermediates. Enzyme actions were completely selective towards the modification of the methyl ketones in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Recently, Gotor-Fernandez et al 71 reported a chemo-enzymatic process by combining a gold( i ) catalyst and enzymes to transform propargylic derivatives into a variety of nor(pseudo)ephedrine derivatives in a regio- and stereoselective way. Ephedrine-type alkaloids are an important family of nitrogen-containing compounds with multiple applications in medicinal chemistry as mimics of adrenaline.…”
Section: Synthesis Of Organic Compounds Through Chemo-enzymatic Casca...mentioning
confidence: 99%
“…Recently, Gotor-Fernandez et al 71 reported a chemo-enzymatic process by combining a gold( i ) catalyst and enzymes to transform propargylic derivatives into a variety of nor(pseudo)ephedrine derivatives in a regio- and stereoselective way. Ephedrine-type alkaloids are an important family of nitrogen-containing compounds with multiple applications in medicinal chemistry as mimics of adrenaline.…”
Section: Synthesis Of Organic Compounds Through Chemo-enzymatic Casca...mentioning
confidence: 99%
“…Besides some chemical synthetic routes, biocatalytic strategies have also been receiving considerable attention mostly due to their high stereoselectivity and the mild reaction conditions. Particularly, amine dehydrogenase-catalyzed asymmetric reductive amination and kinetic resolution are two attractive processes to access chiral amines.…”
Section: Introductionmentioning
confidence: 99%
“…The regio- and stereo-selective synthesis of nor(pseudo)ephedrine derivatives has been achieved using a combination of gold( i ) and enzyme catalysis. 32 The process involved the gold( i )-catalysed hydration of 1-phenylalkynes, followed by asymmetric biotransamination with an amine transaminase (Scheme 4) or bioreduction with an alcohol dehydrogenase. Mutagenesis studies have allowed the rational design of novel methionine sulfoxide reductase A (MsrA) biocatalysts that can perform the kinetic resolution of bulky sulfoxides.…”
mentioning
confidence: 99%